Genetics and extinction and the example of Isle Royale wolves - Hedrick, PW; Robinson, JA; Peterson, RO; Vucetich, JA (Animal Conservation, 2019)
Genetic factors have long been a concern in the extinction and viability of species with the short-term effects focusing on inbreeding depression. Genetic rescue has been suggested as a means to overcome the detrimental effects of inbreeding depression. However, it has been difficult to document the genetic dynamics over time of genetic rescue, inbreeding depression and other genetic relationships in endangered species. We show here using a detailed pedigree and genomic data that genetic rescue in the gray wolf Canis lupus population on Isle Royale had only a temporary positive effect reducing inbreeding depression and then the genetic changes from the immigration event resulted in a population decline and now imminent extinction of the population. Examining the genetic details of this situation shows how genetic dynamics after the initial positive effects of genetic rescue have passed can return a small population to a path toward extinction. Thus, the successful conservation of critically small populations would likely depend on alleviating the cause of having become critically small, such as habitat restoration, or periodic re-application of genetic rescue in a manner that does not result in negative genetic dynamics.